IMPACTOS AMBIENTAIS E SOCIOECONÔMICOS NA CONSTRUÇÃO DE EDIFICAÇÕES EM ÁREAS DE PRESERVAÇÃO PERMANENTE - Weila de Castro Escobar (2024)
The research's central objective is to analyze public civil actions filed by the Public Ministry of the State of Mato Grosso do Sul against the owners of a subdivision on the banks of the Ivinhema River. The study addresses the role of education in sustainable development as a driving force for creating a culture of sustainability, considering the 2030 Agenda and Brazil's international commitment to implementing it. The main question is: does the irregular occupation of the subdivision constitute a violation of the rules that protect Permanent Preservation Areas (APPs), essential for environmental preservation? The research focuses on a stretch of approximately one and a half kilometers, subdivided into 60 lots, where owners built summer and leisure residences, causing deforestation and irregular use of the area. These actions violate current regulations on construction in APPs, which establish guidelines for environmental protection. Riverbanks are classified as permanent preservation areas, subject to strict restrictions according to Brazilian environmental legislation. From the Forest Code (Law No. 4,771/65) to the National Environmental Policy Law (Law No. 6,938/81, articles 3 and 4, among others), restrictions and guidelines for the preservation of water resources are outlined. With the promulgation of the Federal Constitution of 1988, environmental protection was elevated to a position of primary importance. Article 225 of the Constitution guarantees everyone the right to an ecologically balanced environment, essential to quality of life, and imposes the duty to preserve the environment for present and future generations. The research will be carried out using the descriptive, deductive and bibliographic-documentary method, through the study of international, national and regional articles and legal instruments. This study will contribute to the understanding of the application of Brazilian Environmental Law in the protection of fragile areas, such as APPs, and for the defense of the Ivinhema River, a crucial natural resource for Mato Grosso do Sul.